2015
DOI: 10.1093/mnras/stu2569
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution, X-ray outburst and optical/infrared emission of SGR 0501+4516

Abstract: We have analyzed the long-term evolution and the X-ray outburst light curve of SGR 0501+4516 in the frame of the fallback disc model. We have shown that the X-ray luminosity, period and period derivative of this typical soft gamma repeater can be achieved by a neutron star with a large range of initial disc masses provided that the source has a magnetic dipole field of ∼ 1.4 × 10 12 G on the pole of the star. At present, the star is accreting matter from the disc, which has an age ∼ 3 × 10 4 yr, and will remai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The employed distances and periods refer to Appendix B and the McGill catalog (Olausen & Kaspi 2013). the release occurs in the stellar interior (Pons & Rea 2012b;Li & Beloborodov 2015) or in the magnetosphere (Beloborodov & Thompson 2007;Kojima & Kato 2014;Benli et al 2015), or both.…”
Section: Maximum Luminosity and Decay Law Of Transientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The employed distances and periods refer to Appendix B and the McGill catalog (Olausen & Kaspi 2013). the release occurs in the stellar interior (Pons & Rea 2012b;Li & Beloborodov 2015) or in the magnetosphere (Beloborodov & Thompson 2007;Kojima & Kato 2014;Benli et al 2015), or both.…”
Section: Maximum Luminosity and Decay Law Of Transientsmentioning
confidence: 99%
“…Incidentally, the fall-back disk model tries to explain the outbursts in terms of sudden mass accretion (Alpar 2001a;Benli et al 2013Benli et al , 2015. However, in such cases, the luminosity would hit a ceiling at the Eddington limit (∼ 10 38 erg s −1 ) rather than at ∼ 10 36 erg s −1 ; the outburst would decay exponentially (Tanaka & Shibazaki 1996), or sometimes falls abruptly via the propeller effect (Asai et al 2013) rather than in power-law form; and the spectrum around the outburst peak would exhibit clear fluorescence Fe-K line (e.g., EW>100 eV), if the fast initial rise of X-ray outbursts indicates a mass reservoir close to the neutron star.…”
Section: Maximum Luminosity and Decay Law Of Transientsmentioning
confidence: 99%
“…In the same model, it is found that a large fraction of HBRPs and persistent AXP/SGRs have 𝐵 0 in the (10 12 -10 13 ) G range (Benli et al 2015;Benli & Ertan 2016, 2017, 2018a, greater than the 𝐵 0 values estimated for CCOs, RRATs, and XDINs (Ertan et al 2014;Benli & Ertan 2018b). Most of these HBRPs with relatively strong fields evolve from the SP phase to the ASD phase achieving the AXP/SGR properties.…”
Section: Summary Of Resultsmentioning
confidence: 86%
“…Illustrative model curves showing the effects of the initial conditions on the evolutionary curves are plotted in the earlier works (Ertan et al 2009(Ertan et al , 2014Benli et al 2015). We can summarize the effects of the initial conditions (𝑃 0 , 𝐵 0 , and 𝑀 d ) as follows: For the sources that enter the evolution in the ASD phase, the long-term evolution is not sensitive to 𝑃 0 .…”
Section: The Modelmentioning
confidence: 99%
“…where and 1 are the area of the disc illuminated by the pulsar and the area of the disc emitting as a blackbody, respectively. Several uncertainties limit the precision of this estimate: a) the actual radius of pulsars/magnetars ranging between 10 and 14 km for a typical 1.4 solar mass star (Steiner et al 2018), b) the exact pulsar/magnetar blackbody radiation at the equatorial region (where the disc plausibly forms) being about 30% smaller than that of the hot spots and polar cap (Aguilera et al 2008) and c) the actual thickness and energy absorbed by the disc (Benli et al 2015;Shakura & Sunyaev 1973;Lu & Cheng 2002). Finally, the NS blackbody photon gravitational redshift would be of the order of 10%.…”
Section: U 0142+61mentioning
confidence: 99%